Splenectomy and its relation to non-transfusion-transmitted infection in thalassemic patients - Mururul Aisyi; Alan Roland Tumbelaka; Bulan Ginting Munthe; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2016)
Background Splenectomy has been associated with an increased susceptibility to infection. Overwhelming postspelenectomy infec- tion (OPSI) can lead to high mortality. Decreased IgM and tuftsin concentration on splenectomized patients seems to play a role in infection's susceptibility. Many studies have been performed to determine the risk factors of infection in thalassemic patients. Objective To find out morbidity patterns and risk factors for pre- dicting the likelihood of infection in splenectomized thalassemic patients. Methods A retrospective cross sectional study was conducted on confirmed thalassemic children who came to Department of Child Health, Cipto Mangunkusumo Hospital within the period of 1973- 2003. Splenectomized patients were categorized as cases group and non-splenectomized patients as control group. Risk factors for development of common cold and diarrhea were analyzed using chi-square test with level of significance <0.05. Results A total of 300 thalassemic patients, 100 of them were sple- nectomized, were enrolled in this study. The 15-year-age group or above is the most common group underwent splenectomy (35%). Common cold is the most common mild infection in both splenec- tomized group (75%) and non-splenectomized (71%). A significant association was found between the risk of infection and splenec- tomy in thalassemic patients (OR=3.8;CI=2.2;6.62; P=0.000). As- sociation between time after splenectomy and frequency of com- mon cold in thalassemia was significant (OR=2.85;CI=1.16;7.14; P=0.011). Severe infection and acute diarrhea were considered not significantly different between the two groups. Conclusion Splenectomy in thalassemia can increase the sus- ceptibility of non-transfusion-transmitted mild infection. Further study is needed to elaborate this finding